2019
DOI: 10.1108/ecam-09-2018-0375
|View full text |Cite
|
Sign up to set email alerts
|

Application of lean manufacturing tools and techniques for waste reduction in Nigerian bricks production process

Abstract: Purpose Non-value adding activities or wastes in the lean term have been the major challenge of the construction industry. Numerous studies have been conducted to investigate how such wastes can be reduced so as to improve the performance of the construction industry. However, the aspect of bricks production process (BPP) has not been extensively covered. Therefore, the purpose of this paper is to investigate the application of lean manufacturing concepts in BPP with a view to identifying the various wastes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 38 publications
0
16
0
1
Order By: Relevance
“…Phenomenology has been used to examine different aspects of construction management and it is particularly suitable for understanding multi-stakeholder opinion as it is being explored in this study (Ajayi et al, 2016;Ibrahim et al, 2018;Aka et al, 2019;Poleacovschi and Javernick-Will, 2017). Commencing with an in-depth review of existing literature on PPP project finance, experienced stakeholders involved directly in the sourcing and provision of finance for PPP projects in Nigeria were consulted and their insights on the research problem were collected, analyzed and subsequently reported.…”
Section: Methodsmentioning
confidence: 99%
“…Phenomenology has been used to examine different aspects of construction management and it is particularly suitable for understanding multi-stakeholder opinion as it is being explored in this study (Ajayi et al, 2016;Ibrahim et al, 2018;Aka et al, 2019;Poleacovschi and Javernick-Will, 2017). Commencing with an in-depth review of existing literature on PPP project finance, experienced stakeholders involved directly in the sourcing and provision of finance for PPP projects in Nigeria were consulted and their insights on the research problem were collected, analyzed and subsequently reported.…”
Section: Methodsmentioning
confidence: 99%
“…Related to this fact, the first point to emphasize is that changes and improvements in processes must occur continuously in organizations due to the speed at which changes occur in the internal and external organizational environment, and due to the new “requests” and needs arising from customers (Brajer-Marczak, 2014). The second point to note is that, while the organization maintains the practice of continuous improvement over time, the more actions and processes can be analyzed, evaluated, and improved (Aka et al, 2020) what’s imply in greater effectiveness taking into account the results of this work.…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…CI can be defined as the total and continuous involvement of the organization’s employees, by doing small task changes that provoke incremental improvement transformations (Aka et al , 2019). Such transformations are carried out continuously and must be close related to the organizational objectives (Filho and Uzsoy, 2010).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…The concern with making these improvements on a continuous basis and following a certain pattern must be in people's thinking when carrying out their tasks. These theoretical assumptions are based on Filho and Uzsoy (2010),Ingelsson and Mårtensson (2014),Salhieh and Abdallah (2019),Aka et al (2019),Maldonado et al (2020)…”
mentioning
confidence: 99%